Perancangan Sistem Informasi Penyelenggaraan Event Lokakarya dan Seminar (Studi Kasus: UNIKOM Bandung) - Aryansyah, K; Sidik, R (Jurnal Teknologi dan Informasi (JATI), 2020)
Workshops and seminars are a form of organizing scientific events in universities. Workshops and seminars become a knowledge sharing activity from practitioners / experts in certain fields. Organizing events to get success, it would require a good event management. UNIKOM Bandung's information system department organizes workshop and seminars events specifically for students. In practice, problems frequently arise and result in the direct implementation. This study aims to design a management information system for event workshops and seminars that can be solutions to problem solving that exist in organizing events in UNIKOM's information systems department. The study was conducted with a qualitative approach and descriptive method. System development adopts a prototype model with an object oriented system approach. The procedure designed includes the procedure of publication, registration, payment, presence. The results of this study are a web-based event management workshop and seminar information system. The system designed is expected to be able to provide better solution to the problem for the participants or the organizing committee.